“Should Pediatric Septal Surgery and Septorhinoplasty Be Performed for Nasal Obstruction?”—A Systematic Review of the Literature - Howard, Theodore; Williams, Isabelle; Navaratnam, Annakan; Haloob, Nora; Stoenchev, Kostadin; Saleh, Hesham (Facial Plastic Surgery, 2024)
Corrective septal surgery for children with nasal obstruction has historically been avoided due to concern about the impact on the growing nose, with disruption of midfacial growth. However, there is a paucity of data evaluating complication and revision rates post-nasal septal surgery in the pediatric population. In addition, there is evidence to suggest that failure to treat nasal obstruction in children may itself result in facial deformity and/or developmental delay. The aim of this systematic review is to evaluate the efficacy and safety of septal surgery in pediatric patients with nasal obstruction. A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. MEDLINE, Embase, and the Cochrane Library were searched. Original studies in pediatric patients (<18 years of age) with nasal obstruction were eligible for inclusion. Patients with cleft lip or palate as their primary diagnosis were excluded. Our primary outcomes were patient-reported outcome measures (PROMs), postsurgical complications, and revision rates. Secondary outcomes included surgical technique, anatomical considerations, and anthropometric measurements. Eighteen studies were included (1,080 patients). Patients underwent septoplasty, septorhinoplasty, rhinoplasty, or a combination of procedures for nasal obstruction. Obstruction was commonly reported secondary to trauma, nasal septal deviation, or congenital deformity. The mean age of the patients was 13.04 years with an average follow-up of 41.8 months. In all, 5.6% patients required revision surgery and there was an overall complication rate of 7.8%. Septal surgery for nasal obstruction in children has low revision and complication rates. However, a pediatric-specific outcome measure is yet to be determined. Larger prospective studies with long-term follow-up periods are needed to determine the optimal timing of nasal surgery for nasal obstruction in the pediatric population.
Keywords: pediatrics; nasal obstruction; septal surgery; septoplasty; septorhinoplasty; rhinoplasty; systematic review